The national interest: one notion, two speeches put to the testregional integration in Africa - (:unkn) unknown (My University, 2016)
Two observations attract the attention of political analysts: the slowness of the regional integration process in Africa and the preeminence of national interest as a principle of action of the State on the international scene, including its participation in the process of regional integration. Regional integration in Africa has difficulty prospering due to the perception of national interest on the part of States. This analysis aims to elucidate the influence of national interest on the regional integration process in Africa. The notion of national interest is an ambivalent notion which does not require unanimity as to its substantial meaning. According to realists and liberals, it is framed in a selfish way. For constructivists, it requires an altruistic connotation. The participation of States in the integration process in Africa shows that the ambivalence of national interest exerts a double influence on the said process: while selfish national interest slows it down, altruistic national interest is a factor. of dynamisation. In an analytical and explanatory approach, the analysis calls for the exaltation of altruistic national interest to boost said process.
Keywords: African Research